Analysis of stylar ribonucleases (S-Rnases) in an almond progeny of 'Ferralise x Tuono' - Duval H.; Boutard A.; Faurobert M. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Recent studies have demonstrated the interest of stylar ribonucleases electrophoretic patterns for predicting incompatibility S-alleles in almond cultivars. In this work, we have analysed a progeny of 'Ferralise x Tuono'. 'Ferralise' shares the S1 allele with 'Tuono' (S1Sf) and has the same S1S3 genotype than 'Ferragnès'. All tested progeny seedlings, except one, were genotyped S1Sf or S3Sf, and were considered self-compatible. The transmission of self-compatibility from 'Tuono', is similar in the two progenies 'Ferralise x Tuono' and 'Ferragnès x Tuono'.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)